Dried fruit consumption and cardiometabolic health: a randomized crossover trial - Sullivan, Valerie K. (Br J Nutr, 2020)
Fruit intake is associated with lower risk of cardiometabolic diseases. However, effects of dried fruits on cardiometabolic health are not well researched. We investigated the effect of daily dried fruit consumption compared to a carbohydrate-rich snack on cardiometabolic disease risk factors in adults with increased cardiometabolic risk. A two-period randomized crossover trial was conducted in adults (n=55) with elevated BMI and at least one additional risk factor for cardiometabolic disease to compare the effects of consuming 3/4 cup/d mixed dried fruits (plums, figs, dates, and raisins) or a calorie- and carbohydrate-matched control snack for 4 weeks. The primary outcome was low-density lipoprotein cholesterol (LDL-C); secondary outcomes included other lipids and lipoproteins, glucose and insulin, C-reactive protein, blood pressure, and vascular stiffness. Linear mixed models were used for data analysis. Lipid and lipoprotein concentrations did not differ between conditions, however dried fruit increased LDL-C (0.10 mmol/L, 95% CI: 0.01, 0.20) compared to baseline. Compared to the control, dried fruit increased mean fasting glucose (0.08 mmol/L, 95% CI: 0.005, 0.16; P=0.038). Vascular outcomes, fasting insulin, and C-reactive protein did not differ between conditions. Mean weight changes did not differ (P=0.55) but tended to increase after both conditions (dried fruit: 0.3 kg, 95% CI: −0.09, 0.65; control: 0.4 kg, 95% CI: 0.01, 0.75). Thus, short-term daily consumption of a large portion of mixed dried plums, figs, dates, and raisins, without structured dietary guidance, did not improve cardiometabolic risk factors, compared to carbohydrate-rich snacks, in adults with increased baseline cardiometabolic risk.